Survey Data and Subjective Beliefs in Business Cycle Models - Bhandari, Anmol; Borovička, Jaroslav; Ho, Paul (Review of Economic Studies, 2025)
Abstract This paper develops a theory of subjective beliefs that departs from rational expectations, and shows that biases in household beliefs have quantitatively large effects on macroeconomic aggregates. The departures are formalized using model-consistent notions of pessimism and optimism which are supported by extensive time-series and cross-sectional evidence from household surveys. The role subjective beliefs play in aggregate fluctuations is quantified in a business cycle model with goods and labour market frictions. Consistent with the survey evidence, an increase in pessimism generates upward biases in unemployment and inflation forecasts and lowers economic activity. The underlying belief distortions reduce aggregate demand and propagate through frictional goods and labour markets. As a by-product of the analysis, solution techniques that preserve the effects of time-varying belief distortions in the class of linear solutions are developed.